A Multicomponent Exercise Intervention that Reverses Frailty and Improves Cognition, Emotion, and Social Networking in the Community-Dwelling Frail Elderly: A Randomized Clinical Trial - Tarazona-Santabalbina, Francisco José; Gómez-Cabrera, Mari Carmen; Pérez-Ros, Pilar; Martínez-Arnau, Francisco Miguel; Cabo, Helena; Tsaparas, Konstantina; Salvador-Pascual, Andrea; Rodriguez-Mañas, Leocadio; Viña, José (Journal of the American Medical Directors Association, 2016)
Frailty can be an important clinical target to reduce rates of disability. To ascertain if a supervised-facility multicomponent exercise program (MEP) when performed by frail older persons can reverse frailty and improve functionality; cognitive, emotional, and social networking; as well as biological biomarkers of frailty, when compared with a controlled population that received no training. This is an interventional, controlled, simple randomized study. Researchers responsible for data gathering were blinded for this study. Participants from 2 primary rural care centers (Sollana and Carcaixent) of the same health department in Spain were enrolled in the study between December 2013 and September 2014. We randomized a volunteer sample of 100 men and women who were sedentary, with a gait speed lower than 0.8 meters per second and frail (met at least 3 of the frailty phenotype criteria). Participants were randomized to a supervised-facility MEP (n = 51, age = 79.5, SD 3.9) that included proprioception, aerobic, strength, and stretching exercises for 65 minutes, 5 days per week, 24 weeks, or to a control group (n = 49, age = 80.3, SD 3.7). The intervention was performed by 8 experienced physiotherapists or nurses. Protein-calorie and vitamin D supplementation were controlled in both groups. Our MEP reverses frailty (number needed to treat to recover robustness in subjects with attendance to ≥50% of the training sessions was 3.2) and improves functional measurements: Barthel (trained group 91.6 SD 8.0 vs 82.0 SD 11.0 control group), Lawton and Brody (trained group 6.9 SD 0.9 vs 5.7 SD 2.0 control group), Tinetti (trained group 24.5 SD 4.4 vs 21.7 SD 4.5 control group), Short Physical Performance Battery (trained group 9.5 SD 1.8 vs 7.1 SD 2.8 control group), and physical performance test (trained group 23.5 SD 5.9 vs 16.5 SD 5.1 control group) as well as cognitive, emotional, and social networking determinations: Mini-Mental State Examination (trained group 28.9 SD 3.9 vs 25.9 SD 7.3 control group), geriatric depression scale from Yesavage (trained group 2.3 SD 2.2 vs 3.2 SD 2.0 control group), EuroQol quality-of-life scale (trained group 8.2 SD 1.6 vs 7.6 SD 1.3 control group), and Duke social support (trained group 48.5 SD 9.3 vs 41.2 SD 8.5 control group). This program is unique in that it leads to a decrease in the number of visits to primary care physician (trained group 1.3 SD 1.4 vs 2.4 SD 2.9 control group) and to a significant improvement in frailty biomarkers. We have designed a multicomponent exercise intervention that reverses frailty and improves cognition, emotional, and social networking in a controlled population of community-dwelling frail older adults. ClinicalTrials.gov. Identifier: NCT02331459.